2023
DOI: 10.3389/fendo.2023.1078660
|View full text |Cite
|
Sign up to set email alerts
|

Corneal dendritic cells in diabetes mellitus: A narrative review

Abstract: Diabetes mellitus is a global public health problem with both macrovascular and microvascular complications, such as diabetic corneal neuropathy (DCN). Using in-vivo confocal microscopy, corneal nerve changes in DCN patients can be examined. Additionally, changes in the morphology and quantity of corneal dendritic cells (DCs) in diabetic corneas have also been observed. DCs are bone marrow-derived antigen-presenting cells that serve both immunological and non-immunological roles in human corneas. However, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 114 publications
0
3
0
Order By: Relevance
“…Cytokines and growth factors secreted in response to nerve injury and inflammation also activate the usual quiescent keratocytes, gaining replicative, migratory, and contractile properties, which cumulatively manifest as hyper-reflective keratocytes [42,43]. Dendritic cells are the most potent antigen-presenting cells in the body, and increased mature dendritic cells are seen in active corneal inflammation [44,45]. Barros et al reported that dendritic cells were found in corneas in almost 70% of post-COVID patients, with a predilection for younger, asymptomatic patients [25].…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines and growth factors secreted in response to nerve injury and inflammation also activate the usual quiescent keratocytes, gaining replicative, migratory, and contractile properties, which cumulatively manifest as hyper-reflective keratocytes [42,43]. Dendritic cells are the most potent antigen-presenting cells in the body, and increased mature dendritic cells are seen in active corneal inflammation [44,45]. Barros et al reported that dendritic cells were found in corneas in almost 70% of post-COVID patients, with a predilection for younger, asymptomatic patients [25].…”
Section: Discussionmentioning
confidence: 99%
“…Corneal epithelial cells, dendritic cells, and cornea sensory neurons are anatomically and structurally intimately connected, a concept of epithelium–nerve–dendritic cells (epineuroimmune) function unit, which is analogous to the neurovascular function unit in the retina, which consists of glia, vasculature, and neurons, has been proposed [ 48 ]. So far, little is known about the physiological mechanisms of intercommunication between the components of this unit, to the point of questioning which of them initially detects the injuries or alterations and induces changes in the other two components [ 69 ]. The microbiota of the ocular surface is composed of microorganisms that colonize the cornea and conjunctiva [ 70 ].…”
Section: Ocular Surface Innate Immunitymentioning
confidence: 99%
“…DM presents as a low-grade chronic in ammatory pathology. In ammation plays a pivotal role in the development and progression of diabetic eye disease (DED), in conjunction with increases in proin ammatory mediators, apoptosis, and vascular permeability (Asiedu et al 2022;Liu et al 2023). Current research on the link between in ammation and DED has focused on DR and DME.…”
Section: Introductionmentioning
confidence: 99%